Quantitative and Rapid Antibacterial Assay of Micromeria biflora Benth. Leaf Essential Oil Against Dental Caries Causing Bacteria Using Phylogenetic Approach - Amritesh Chandra Shukla2, Pravin Tiwari3; Anupam Dikshit1*, Rohit Kumar Mishra1, Awadhesh Kumar1, (Journal of Ecobiotechnology, 2010)
<table class="MsoNormalTable" style="border-collapse: collapse; mso-border-top-alt: solid black 1.5pt; mso-border-bottom-alt: solid black 1.5pt; mso-yfti-tbllook: 1184; mso-padding-alt: 0in 5.4pt 0in 5.4pt;" border="1" cellspacing="0" cellpadding="0"> <td style="border-right: #c0c0c0; padding-right: 5.4pt; border-top: black 1.5pt solid; padding-left: 5.4pt; padding-bottom: 0in; border-left: #c0c0c0; width: 349.25pt; padding-top: 0in; border-bottom: black 1pt solid; background-color: transparent; mso-border-top-alt: solid black 1.5pt; mso-border-bottom-alt: solid black .75pt;" width="582" valign="top"> Abstract The phylogenetic relationship of four dental caries causing bacterial pathogens has been studied using ITS1 sequences of the standard strains were aligned by using the ClustalW computer program. The essential oil obtained from the leaves of Micromeria biflora Benth., obtained by hydrodistillaton. The chemical compositions of the essential oil from Micromeria biflora Benth was analyzed by gas chromatography-mass spectrometry (GC-MS). The GC/MS analysis showed eight major active constituents in the leaf essential oil of Micromeria biflora Benth. The antibacterial activity of the oil was evaluated against four dental caries causing bacteria such as Streptococcus mutans (MTCC 890); Lactobacillus acidophilus (MTCC 447); Streptococcus mitis (MTCC 2695) and Streptococcus salivarius (MTCC 1938) using broth microdilution method recommended by Clinical Laboratory Standards Institute (CLSI) formely (NCCLS). Itâ€™s showed excellent activity against Streptococcus mutans with their Minimum inhibition concentration (MIC) 0.15 mg/ml and (IC50) 0.10 mg/ml and less effective against Lactobacillus acidophilus. The essential oil of Micromeria biflora Benth from leaf has played a significant role against dental caries causing bacteria. Relationships of the dental caries causing pathogens to the toxicity of the oil vis-Ã -vis phylogeny using molecular data of pathogens have also been discussed. Â 1Biological Product Laboratory, Dept. of Botany, University of Allahabad, Allahabad-211002 2Dept. of Horticulture, Aromatic & Medicinal Plants, Mizoram University, Aizawl-796009, India 3Dental Surgeon, Saumya Dental Clinic, Taigore Town, Allahabad, India *Corresponding author, Email: anupambplau@rediffmail.com, Tel: +919335108519 Please Cite This Article As: Â Rohit Kumar Mishra, Awadhesh Kumar, Amritesh Chandra Shukla, Pravin Tiwari and Anupam Dikshit. 2010. Quantitative and Rapid Antibacterial Assay of Micromeria biflora Benth. Leaf Essential Oil Against Dental Caries Causing Bacteria Using Phylogenetic Approach. J. Ecobiotechnol. 2(4):22-26.